Mechanical and in vitro biological properties of uniform and graded Cobalt‐chrome lattice structures in orthopedic implants. Issue 12 (8th May 2021) - Pagani, Stefania; Liverani, Erica; Giavaresi, Gianluca; De Luca, Angela; Belvedere, Claudio; Fortunato, Alessandro; Leardini, Alberto; Fini, Milena; Tomesani, Luca; Caravaggi, Paolo
Abstract: Human bones are biological examples of functionally graded lattice capable to withstand large in vivo loading and allowing optimal stress distribution. Disruption of bone integrity may require biocompatible implants capable to restore the original bone structure and properties. This study aimed at comparing mechanical properties and biological behavior in vitro of uniform (POR‐FIX) and graded (POR‐VAR) Cobalt‐chrome alloy lattice structures manufactured via Selective Laser Melting. In compression, the POR‐VAR equivalent maximum stress was about 2.5 times lower than that of the POR‐FIX. According to the DIC analysis, the graded lattice structures showed a stratified deformation associated to unit cells variation. At each timepoint, osteoblast cells were observed to colonize the surface and the first layer of both scaffolds. Cell activity was always significantly higher in the POR‐VAR ( p  < 0.0005). In terms of gene expression, the OPG/RANKL ratio increased significantly over time ( p  < 0.0005) whereas IL1β and COX2 significantly decreased (7 day vs 1 day; p  < 0.0005) in both scaffolds. Both uniform‐ and graded‐porosity scaffolds provided a suitable environment for osteoblasts colonization and proliferation, but graded structures seem to represent a better solution to improve stress distribution between implant and bone of orthopedic implants.